Dynamic MLOps Framework with Integrated CLI for Automated ML Project Inception, Kafka-Driven Real-Time Model Monitoring, and Adaptive Canary Deployment Architectures - Kozák, Tomáš; Galindez Arias, William Arley; Vencovský, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
The thesis introduces a Python framework and library with an integrated CLI, designed to streamline ML lifecycle management by automating project inception, real-time model monitoring, and adaptive canary deployment processes. The library facilitates automated project setup across various configurable ML paradigms (whether it is a Random Forest classification, XGBoost regression, T5-based time-series forecasting, encoder-only / encoder-decoder / decoder-only transformer-based NLP downstream tasks, or practically any other configurable ML paradigm) with optimized directories, subdirectories and configuration files adhering to recommended practices in ML development. The library features a plugin architecture for extensibility, allowing integration with other core components / packages, such as real-time model monitoring with anomaly detection mechanisms, adaptive canary deployment architectures, and integrated UI for monitoring and deployment control. Model monitoring is implemented using high-throughput, low-latency data streaming tool Apache Kafka. Deployed ML models act as Kafka producers, emitting real-time inference data and performance metrics serialized with Apache Avro for schema enforcement and efficiency. Model monitoring is accompanied with anomaly, data, and concept drift detection mechanisms via techniques like PSI, Isolation Forests, or LSTM auto-encoders. Adaptive canary deployment architectures and strategies are implemented specifically for ML models.
Vedoucí práce: William Arley Galindez Arias
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data a analytika pro business [obor dipl. práce]; diplomové práce; master's theses